Production of Biochar from Sago Dregs Using NaOH Pretreatment and Microwave Pyrolysis - Syam, Jabal Nur; Diyah, Yumeina; Salengke, Salengke (Salaga Journal, 2025)
The waste from sago dregs generated during the starch extraction process has not been optimally utilized and has the potential to cause environmental pollution. This study aimed to process sago dregs into biochar through chemical pretreatment (NaOH soaking) and physical pretreatment (microwave pyrolysis) and applied it as raw material for briquettes. The research methods consisted of (1) Pretreatment of sago dregs with 10% and 30% NaOH for 6 hours, (2) Pyrolysis using a 540-watt microwave at 300–400°C for 20 minutes, and (3) Briquette production using sago starch binder at a 10:1 ratio. The analysis results indicated that 30% NaOH pretreatment significantly reduced cellulose, hemicellulose, and lignin contents to 1.07, 0.52, and 1.10%, respectively, compared to the 10% NaOH (6.11%, 5.71%, and 6.03%). The moisture content of biochar decreased to 2.53–2.65%, in accordance to SNI 06-3730-1995 standard of 10% maximum . However, the ash content increased to 45.99–53.78%, exceeding the SNI limit of 15%. Briquettes made from 30% NaOH-pretreated biochar had the longest burning time (26.54 minutes), outperforming the 10% NaOH (12.32 minutes). This study found that sago dregs have the potential to serve as a high-quality biochar raw material due to its moisture content meets the SNI standard, although its high ash content limits its use as fuel. Sago dregs biochar briquettes can be considered a renewable energy alternative, while the high ash content offers potential applications in soil or water remediation.